HUBUNGAN KESEJAHTERAAN PSIKOLOGIS DENGAN KOMPETENSI GURU DI YAYASAN HAJI MAKSUM ABIDIN SHALEH STABAT - Pradana Chairy Azhar (Jurnal Sintaksis, 2019)
The students aims to find out the relationship between Psychological Well-Being with Teachers’ Competence of Yayasan Haji Maksum Abidin Shaleh while the samples are 91 teachers, research conducted on 56 teachers. The data collection did by using scales including two scales there are Psychological Well-Being scale, and teachers’ competence scale. The data analysis method that used is Multiple Regression Analysis. From result of data analysis found that there is a significance of positive correlation between Psychological Well-Being with teachers’ competence of Yayasan Haji Maksum Abidin Shaleh, that is shown by coefificient F=9,324 with P<0,05.Psychological Well-Being gives contribute to Teachers’ Competence as much as 23,0%.From the result above so it hopes to Yayasan Haji Maksum Abidin Shaleh to increase the better Psychological Well-Being, the fulfillment of psychological well-being so the contribution in carrying out the responsibilities in teaching will achieve for increase teachers’ competence in education world, creates new inventions, creative, and be motivator.